Climate Change Scenarios for Hudson Bay, Canada, from General Circulation Models - Gough, William A.; Wolfe, Edmund (ARCTIC, 2001)
Two generations of a climate model are compared using the impact of a CO2 doubling on the Hudson Bay region as the means of diagnosing differences in model performance. Surface temperature, precipitation, sea-ice coverage, and permafrost distribution are compared. The most striking difference is the response of the sea ice in the two models. In the coupled atmosphere-ocean climate model, sea ice virtually disappears in Hudson Bay. This leads to a substantially higher regional temperature response. We suggest that conductivity of sea ice and thermal diffusivity of seawater are key factors that cause the difference in sea-ice response. It is recommended that a regional model be developed to produce more representative climate change scenarios for the Hudson Bay region. On compare deux générations d'un modèle de climat en calculant l'incidence sur la région de la baie d'Hudson d'une multiplication par deux du taux de CO2 afin de diagnostiquer les différences dans la performance des deux versions du modèle. On compare la température en surface, les précipitations, la couverture de glace de mer et la distribution du pergélisol. La différence la plus marquante apparaît dans la façon dont la glace de mer réagit dans les deux modèles. Dans le modèle de climat avec couplage atmosphère-océan, la glace de mer disparaît pratiquement de la baie d'Hudson. Il en résulte une hausse notable de la température régionale. On suggère que la conductivité de la glace de mer et la diffusivité thermique de l'eau de mer sont des facteurs clés responsables de la différence dans le comportement de la glace de mer. On recommande l'élaboration d'un modèle régional qui créerait des scénarios de changement climatique plus réalistes pour la région de la baie d'Hudson.